The native parasitoids exploiting the invasive leafminer Coptodisca lucifluella (Lepidoptera: Heliozelidae) in Southern Russia and Abkhazia - Oksana V. Kosheleva; Elena N. Zhuravleva; Natalia N. Karpun; Natalia I. Kirichenko (Acta Biologica Sibirica, 2025)
The leafmining moth Coptodisca lucifluella (Lepidoptera: Heliozelidae) is the North American species, which recently invaded Europe. Here, we provide first data on the parasitoid assemblage associated with this leafminer in Southern Russia and Abkhazia. In 2024, altogether 28 parasitoid specimens were reared from the late-instar larvae and pupae of C. lucifluella and identified to seven parasitic wasp species. Among them, six species were from Eulophidae: Pnigalio soemius (Walker), Cirrospilus variegatus (Masi), C. viticola (Rondani), Chrysocharis pentheus (Walker), Closterocerus sp. (presumably new species to science), Minotetrastichus frontalis (Nees) and one from Eupelmidae: presumably Eupelmus kiefferi De Stefani. All these parasitoids are native to the studied area and have been documented on C. lucifluella for the first time. In Russia and Abkhazia, the parasitism rates reached 13% and 31%, respectively. Four species contributed the most to the leafminer mortality: M. frontalis (11 out of 13%) in Sochi (Russia), C. pentheus (12 out of 31%), C. viticola (8%), and C. variegatus (8%) in Gagra (Abkhazia). For the recorded parasitoids, the distribution and hosts are mentioned, and the original photographs of parasitoid adults are provided. Additionally, an exhaustive checklist of parasitoids associated with C. lucifluella in its modern range was compiled, accounting 32 species. Altogether, our findings suggest that during the invasion, C. lucifluella escaped from its aborigine enemies but became a target for the parasitoids naturally present in Southern Russia and Abkhazia.